ANALISIS TINGKAT SUKU BUNGA KOPERASI DAN KUALITAS LAYANAN TERHADAP KEPUASAN ANGGOTA DALAM MELAKUKAN PINJAMAN MODAL USAHA DI KABUPATEN SRAGEN: Studi Kasus pada Koperasi Simpan Pinjam Karya Eka Warsa Tanggel Cabang Gemolong - Wiwin Handayani; Suyatmin Waskito Adi (LP2M Universitas Bina Bangsa, 2024)
Member satisfaction is a level at which the needs, desires and expectations of customers can be met which will result in repeat purchases or continued loyalty. This study aims to determine the influence of cooperative interest rates and service quality on member satisfaction in making business capital loans in Sragen Regency. The approach used in this study is quantitative research. The data collection technique in this study is by using a survey to parties in the Karya Eka Warsa Tanggel Cooperative, Gemolong Branch, Sragen Regency. The population of this study is in members of the Cooperative by Eka Warsa Tanggel Gemolong Branch The sampling method used is purposive sampling. purposive sampling. The data analysis method used is a multiple linear regression analysis model. The results showed that the variable interest rate and service quality had a significant effect on member satisfaction